Les premiers comparatistes et l'inachèvement linguistique de la France: Le problème de l'occitan - Claudon, Francis (Verbum – Analecta Neolatina, 2007)
This paper deals with the question of the linguistic unity of France from a diachronic viewpoint. Until the end of the 18th century, intellectuals, educators (Rollin, La Harpe, Noel and La Place) always emphasized the fact that in France people spoke French, which is not entirely true, for the whole South had been speaking a different language from that spoken in Paris for a long time. Still, at the beginning of the 19th century, Thiers, Stendhal, considered Provence, Langedoc, the South-West of France, as a far-off, under-developed country. It was in this context that the first French comparatists appeared. Fauriel, J. J. Ampère, and a few others (Raynouard) contributed in this way to the birth of Provençal and Occitan studies. At the same time, they dispelled the myth of a France that would linguistically and culturally be heir to Rome and Latinity. Even the stance of Maurras, for instance, is complex: himself a southerner, the herald of romanic culture, he explains in his memoirs how much he hesitated between the two languages, at the time of the Félibrige movement. The end of this prolonged cultural autonomy coincided with the soar of Symbolism. Nonetheless, the French comparatists began their career by distinguishing reality from myths, in a purely French debate which still retains today some secret intricacies.